Features of laboratory indicators of severe community-acquired pneumonia - Pertzeva T.A.; Avramenko I.V. (Medičnì Perspektivi)
Based on data from the prospective analysis of patients with severe community-acquired pneumonia over the year of observation, the article presents data on the features of laboratory indicators of the course of severe community-acquired pneumonia. Patients included in the study were hospitalized in the pulmonology department (or therapy), and in the intensive care unit of three clinical hospitals in the city of Dnipro, namely, the Dnipropetrovsk City Clinical Hospital N 6, the Dnipropetrovsk City Clinical Hospital N 2, the Dnipropetrovsk City Clinical Hospital N 16, which are the clinical bases of the SE “Dnipropetrovsk medical academy of Health Ministry of Ukraine”. In the course of studies, the dependence of the severity of patients' state on the severity of inflammatory markers and fibrosis markers was shown. The effect of the prognostic significance of the level of the enzyme TGFβ and C-reactive protein (CRP) for the evaluation of possibility of formation of long-term pathological changes after a severe community-acquired pneumonia has been examined. It was established that a high level of CRP (38.3 [11.3, 150.9] mg / L) and TGFβ (20149.1±424.0 pg/ml) in the blood plasma of patients can be considered as an additional marker of the severity of the course of community-acquired pneumonia. The results can be the basis for a more individual approach to the development of diagnostic and therapeutic programs for patients with severe community-acquired pneumonia.